Increasing Teacher Commitment through HR Planning: Peningkatan Komitmen Guru melalui Perencanaan SDM - Isa, Muzakar; Wajdi, M. Farid; Huda, Miftakhul; Amir, Rafiq Arkana (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Organization experiences job vacancies due to various factors and decides to recruit new employees; the initial step to be taken is to identify the job characteristics and competencies required from individuals capable of performing the tasks. Employee performance motivation is heavily influenced by the enthusiasm and work actions of the leaders. If a leader demonstrates genuine dedication and full commitment to a task, it directly triggers the enthusiasm of employees or subordinates to actively assist the leader in achieving the organizational goals. To enhance the performance and competitiveness of MIM PK Wirogunan towards becoming an excellent madrasah, highly committed and loyal teachers are required, necessitating a better concept of human resource management. Every educational institution must plan the sustainability of its programs. During the operational process, every educational institution faces several challenges and issues. The changing conditions of competition, shifts in demand, and educational needs in society need to be managed attentively. To support the performance of MIM PK Wirogunan, training in human resource planning (job analysis), salary formulation, and teacher career development are essential.